Electricity, heat, and gas sector data for modeling the German system - Friedrich Kunz; Mario Kendziorski; Wolf-Peter Schill; Jens Weibezahn; Jan Zepter; Christian R. von Hirschhausen; Philipp Hauser; Matthias Zech; Dominik Möst; Sina Heidari; Björn Felten; Christoph Weber (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
[Introduction] This data documentation describes a data set of the German electricity, heat, and natural gas sectors compiled within the research project `LKD-EU' (Long-term planning and short-term optimization of the German electricity system within the European framework: Further development of methods and models to analyze the electricity system including the heat and gas sector). The project is a joined effort by the German Institute for Economic Research (DIW Berlin), the Workgroup for Infrastructure Policy (WIP) at Technische Universität Berlin (TUB), the Chair of Energy Economics (EE2) at Technische Universität Dresden (TUD), and the House of Energy Markets & Finance at University of Duisburg-Essen. The project was funded by the German Federal Ministry for Economic Affairs and Energy through the grant `LKD-EU', FKZ 03ET4028A. The objective of this paper is to document a reference data set representing the status quo of the German energy sector. We also update and extend parts of the previous DIW Data Documentation 75 (Egerer et al. 2014). While the focus is on the electricity sector, the heat and natural gas sectors are covered as well. With this reference data set, we aim to increase the transparency of energy infrastructure data in Germany. On the one hand, this documentation presents sources of original data and information used for the data set. On the other hand, it elaborates on the methodologies which have been applied to derive the data from respective sources in order to make it useful for modeling purposes and to promote a discussion about the underlying assumptions. Furthermore, we briefly discuss the underlying regulations with regard to data transparency in the energy sector. Where not otherwise stated, the data included in this report is given with reference to the year 2015 for Germany. This document is structured as follows: Section 2 describes data of the German electricity sector and explains the methods for deriving this data. Section 3 discusses the data preparation for German heating networks. Section 4 covers the natural gas system in Germany. While Sections 2 to 4 focus on Germany, interactions on a European level are considered in a stylized way. Finally, Section 5 introduces some research questions to be answered with the help of the presented data set and discusses a range of limitations. The data set described in the following chapters can be downloaded from the Zenodo repository under the DOI https://doi.org/10.5281/zenodo.1044463.
doi:10.5281/zenodo.1044463
Keywords: 330